PUPIL´S SELF-REFLEXTION IN TECHNICAL EDUCATION AT PRIMARY SCHOOL - CASTKOVA, Pavlina; STOLINSKA, Dominika (Trends in education, 2014)
The paper presents the importance of pupil´s self-reflection, which is directed by teacher as an integral part of the educational process at primary school. The issue is addressed in the context of technical education and its specificities on the basis of current educational trends. The aim of this paper is to highlight the importance of pupil´s self-reflection in an attempt to be the improvement of the educational process through self-reflective items, which are formulated on three levels cognitive, behavioral, affective.
Keywords: technical education; primary school; self-reflection; evaluation.